The Exploring the Influence of Perceived Value on Customer Loyalty: The Mediating Role of Emotional and Social Value in Driving Satisfaction and Repeat Purchase Intention. Evidence from PT. BPR Ekadharma Bhinaraharja, East Java, Indonesia - Bahagio, Dwi Atmodjo; Adilla, Fitroh; Setiawan, Zunan (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study examines how perceived value influences consumer loyalty for the “Kilau Emas” product offered by PT. BPR Ekadharma Bhinaraharja (East Java, Indonesia). The model foregrounds emotional value and social value as mediators, together with overall customer satisfaction, to clarify the mechanisms through which perceived value translates into repurchase intention and loyalty. Cross-sectional survey was administered to a purposive sample of active “Kilau Emas” customers (N = 412). Measurement instruments were adapted from validated scales in prior studies and translated into Indonesian, then pilot-tested. Constructs were modeled as follows: Perceived Value (exogenous), Emotional Value & Social Value (mediators), Customer Satisfaction (mediator), and Repurchase Intention / Consumer Loyalty (endogenous). The findings suggest that perceived value increases repurchase intention primarily indirectly—through emotional and social value that bolster customer satisfaction—rather than through a strong direct effect. Emotional value emerges as the dominant mediating pathway, indicating that for “Kilau Emas” customers, affective resonance (feeling valued, proud, emotionally connected) matters more than purely functional considerations. Managerially, community banks should therefore prioritize experience design that cultivates authentic emotional and social meaning (e.g., locally rooted storytelling, personalized service rituals, community recognition programs) to convert perceived value into durable loyalty. The model’s R² values indicate substantial explanatory power, supporting the practical usability of the framework for predictive and strategic decision-making.